INVESTIGASI PENGARUH KOMPOSISI DEWAN DAN KONSENTRASI KEPEMILIKAN PADA KUALITAS PENGUNGKAPAN LAPORAN KEUANGAN - Citrawati Jatiningrum; Fauzi Fauzi; Bernadhita H.S Utami (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2022)
Crucial issues in Asia occur when modern companies are majority owned by large shareholders and effectively control the company. This phenomenon will lead to type II agency conflict, its happens conflict between the majority shareholder and the minority shareholder. This study aims to investigate the effect of the board composition and concentrated ownership on the disclosure quality of financial statement. The samples selected are companies in Indonesia with concentrated ownership. This study uses multiple regression analysis method with the statistical test result reveal that the concentration of ownership has a negative effect on the disclosure quality, while the board composition has a significant positive effect on the quality of disclosure. However, independent commissioners have no influence on the quality of financial statements. This study provides evidence that the concentration of ownership and board composition has an impact on the disclosure quality in Indonesian companies. This finding can be consideration for regulators and policy makers for improving good corporate governance and review the disclosure requirements of financial statements as a form of protection for minority shareholders.